2017
DOI: 10.1021/acsnano.7b05885
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon-Inspired Mechanochromic Photonic Films Composed of Non-Close-Packed Colloidal Arrays

Abstract: Chameleons use a non-close-packed array of guanine nanocrystals in iridophores to develop and tune skin colors in the full visible range. Inspired by the biological process uncovered in panther chameleons, we designed photonic films containing a non-close-packed face-centered-cubic array of silica particles embedded in an elastomer. The non-close-packed array is formed by interparticle repulsion exerted by solvation layers on the particle surface, which is rapidly captured in the elastomer by photocuring of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
265
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(269 citation statements)
references
References 41 publications
3
265
1
Order By: Relevance
“…Second, a hydrogel monomer can be induced into the dispersion medium to lock the cross‐linked network‐like solid hydrogel through photopolymerization . As shown in Figure , the locked SiO 2 colloidal particles into an elastomer can effectively form a nonclose‐packed PCS (NCPP) array . By this way, the problem of low elastic modulus in NCPP colloidal particles will be settled as it has been proven that NCPPs possess better optical properties than their close‐packed counterparts …”
Section: Fabrication Of Structural Color Materials By Colloidal Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a hydrogel monomer can be induced into the dispersion medium to lock the cross‐linked network‐like solid hydrogel through photopolymerization . As shown in Figure , the locked SiO 2 colloidal particles into an elastomer can effectively form a nonclose‐packed PCS (NCPP) array . By this way, the problem of low elastic modulus in NCPP colloidal particles will be settled as it has been proven that NCPPs possess better optical properties than their close‐packed counterparts …”
Section: Fabrication Of Structural Color Materials By Colloidal Assemblymentioning
confidence: 99%
“…Photonic films containing a nonclose‐packed fcc array of SiPs embedded in an elastomer, in which inelastic particles enable elastic deformation and reversible color change, as chameleons do. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Fabrication Of Structural Color Materials By Colloidal Assemblymentioning
confidence: 99%
“…PhCs, which feature characteristic reflection peaks cause by their periodic structure, have been utilized as encoding elements for multiplexed analysis . The resultant PhC barcodes have the advantages of stable encoding information and freedom from disturbances in the surface covering . Compared to enzyme‐based rolling‐circle amplification approaches in our previous work, the enzyme‐free HCR appears to offer a low‐cost and reproducible amplification method for genomic and proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Them ajority of the research on photonic crystal elastomers has employed synthetic opals, such as SiO 2 and polystyrene,a nd inverse opals as the photonic crystal component. [3][4][5][6][7][8][9][10] However,weare not limited to synthetic materials to produce photonic crystals.N ature has evolved to produce biomaterials with structural color from chitin nanocrystals in the jewel beetle, [11] guanine nanocrystals in the panther chameleon [12] and cellulose in Pollia condensata. [13] Cellulose is ap articularly attractive building block for photonic crystal applications as it is the most abundant biopolymer and research has demonstrated that we can prepare photonic crystals from cellulose nanocrystals (CNCs).…”
mentioning
confidence: 99%
“…Materials that respond to their environment while also producing avisible readout to the user are desirable for use in optical devices and sensors.One strategy employed to achieve this goal is to use photonic crystals,astheir periodic structure alters how light interacts with the material, giving rise to structural color.T his structure-dependent color is extremely beneficial as it can be tuned, will not fade and does not require the use of toxic dyes. [1,2] Thei ntegration of photonic crystals into elastomers enables their color to be manipulated with the application of mechanical stress,producing materials with dynamic optical properties,w hich have potential applications as mechanical sensors, [3][4][5] optical coatings, [6,7] soft displays [8] and biosensors. [9] Them ajority of the research on photonic crystal elastomers has employed synthetic opals, such as SiO 2 and polystyrene,a nd inverse opals as the photonic crystal component.…”
mentioning
confidence: 99%